A kinematic analysis of the two types of soccer throw-in techniques - Abd-Al-Karem Radwan, Omar; A’mir, Omar; Abdel Fattah, Osama; Hashem Jaber, Osama; Mohammad Ermely, Ziyad; Asri Al-Saoud, Hasan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to identify kinematic variables in two soccer throw-in techniques, examine their relationship to throw distance, and explore differences based on technique. A descriptive approach was used, with a purposive sample of 15 first-grade players from the Hussein Youth Club. Each player performed both types of throw-in techniques, recorded at 60 f/s using a Nikon D3400 camera placed laterally. A total of 30 successful attempts were analyzed using Kinovea 0.8.27 x64. Variables studied included foot distance, skill duration, release velocity and angle, and ball release height. Data were analyzed with SPSS. The results revealed weaknesses in the side throw-in technique, such as a low release angle, though better distances were achieved with the second technique. Significant correlations were found between foot distance, release angle, release velocity, vertical velocity, and throw distance (p<0.05). There were also statistically significant differences in knee angle, moment of throw, and throw distance, favoring the second technique (p<0.05). The sample’s technique shows several weaknesses impacting performance. Projectile variables strongly influence throw distance, closely linked to various kinematic factors. Moreover, the throw-in method is crucial in determining the overall distance.